The Place of Doira Instrument in Uzbek National Art - Ismoil Rustamov (Genius Journals, 2022)
This article discusses the Uzbek folk instrument doira and its role in the performance of our national works.
Keywords: Uzbek national art; doira; tattoo; classical music